2011
DOI: 10.3945/ajcn.110.004515
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in the FADS gene cluster are associated with arachidonic acid concentrations of human breast milk at 1.5 and 6 mo postpartum and influence the course of milk dodecanoic, tetracosenoic, and trans-9-octadecenoic acid concentrations over the duration of lactation

Abstract: Maternal FADS genotypes are associated with breast-milk AA concentrations and might therefore influence the supply of this FA for children. Furthermore, our data indicate an interrelation between the LC-PUFA pathway and saturated and monounsaturated FAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 41 publications
4
78
0
1
Order By: Relevance
“…The second limitation is that we were not able to estimate PUFA levels throughout breastfeeding duration, since mature breast milk was not collected in the EDEN study. Both randomized controlled trials and observational studies support that PUFA levels vary during the course of lactation, depending on maternal diet and fat storage, as well as genetic determinants of de novo biosynthesis (17)(18)(19)(20). In our analysis, we used PUFA levels in colostrum as a proxy of postnatal PUFA exposure, considering that women with higher levels of a given PUFA in colostrum are likely to remain with higher levels in mature milk compared to their counterparts, as long as they keep on the same type of diet.…”
Section: Discussionmentioning
confidence: 99%
“…The second limitation is that we were not able to estimate PUFA levels throughout breastfeeding duration, since mature breast milk was not collected in the EDEN study. Both randomized controlled trials and observational studies support that PUFA levels vary during the course of lactation, depending on maternal diet and fat storage, as well as genetic determinants of de novo biosynthesis (17)(18)(19)(20). In our analysis, we used PUFA levels in colostrum as a proxy of postnatal PUFA exposure, considering that women with higher levels of a given PUFA in colostrum are likely to remain with higher levels in mature milk compared to their counterparts, as long as they keep on the same type of diet.…”
Section: Discussionmentioning
confidence: 99%
“…These long-chain polyunsaturated fatty acids (LC-PUFAs) accumulate in the brain in abundance from the third trimester to 18 months postpartum and are essential for neurogenesis, neurotransmission, and protection from oxidative stress. [51][52][53] The candidacy of FADS2 as a risk modulator for preterm brain injury is raised because FADS2 gene variants have functional effects on LC-PUFA availability, with minor allele carriage at common SNPs including rs174576 being associated with altered levels of arachidonic acid and docosohexaeneoic acid in phospholipid, serum, and breast milk, [54][55][56][57][58] and FADS2 variants may interact with early dietary exposures to influence childhood IQ. 34,35 We found that minor allele carriage at rs174576 is associated with lower FA in white matter, after controlling for nongenetic confounders.…”
Section: Figurementioning
confidence: 99%
“…Breast milk compositions vary with maternal diet, lifestyle, genetic determinants, and the duration of lactation [1,2,3,4,5]. However, little is known whether interindividual differences in human milk composition may induce relevant effects on infant growth and health outcomes.…”
Section: Introductionmentioning
confidence: 99%